Analysis of Student’s Initial Concept on Genetic Material in Pontianak City - Lestari, Aini; Candramila, Wolly (Jurnal Pendidikan MIPA, 2023)
Abstract: This research aims to determine the initial concepts and knowledge source factors that have the greatest influence on student’s understanding on genetic material in Pontianak City. This is a descriptive research with a quantitative approach. Samples are 90 second-grade students at State High Schools in Pontianak City. The instruments used were a diagnostic test consisting of 25 multiple choice questions and a Response Certainty Index (CRI) as well as a genetic knowledge source questionnaire. The test results are analyzed by categorizing students' conceptual understanding based on correct or incorrect answers and low or high CRI scores which are then grouped into understanding the concept, not understanding the concept, guessing, and misconceptions. Student answers showed that only 29% understood the concept, 27% did not understand, 12% guessed, and 32% had misconceptions. School teachers are the highest source of knowledge at 79%, and the study group is the lowest at 22%. The percentage of students who understand the concept is lower than students who do not understand, guess and experience misconceptions, so teachers must handle class XII optimally, for example by planning the best learning models and media to overcome the low understanding of genetic concepts among students at school. Keywords: certainty of response index (CRI), genetics material, initial concept, student’s understanding. Abstrak: Penelitian ini bertujuan untuk mengetahui konsep awal dan faktor sumber pengetahuan yang mempunyai pengaruh paling besar terhadap pemahaman siswa pada materi genetika di Kota Pontianak. Penelitian ini merupakan penelitian deskriptif dan menggunakan pendekatan kuantitatif. Sampel adalah 90 orang siswa SMA Negeri kelas XI di Kota Pontianak. Instrumen yang digunakan adalah tes diagnostik yang terdiri dari 25 soal dan Indeks Kepastian Respon (CRI) serta angket sumber pengetahuan genetik. Hasil tes dianalisis dengan mengkategorikan pemahaman konsep siswa berdasarkan jawaban benar atau salah dan nilai CRI rendah atau tinggi yang kemudian dikelompokkan menjadi memahami konsep, tidak memahami konsep, tebakan, dan miskonsepsi. Jawaban siswa menunjukkan bahwa hanya 29% yang memahami konsep, 27% tidak memahami, 12% menebak, dan 32% mengalami miskonsepsi. Guru sekolah merupakan sumber pengetahuan tertinggi sebesar 79%, dan kelompok belajar terendah sebesar 22%. Persentase siswa yang memahami konsep lebih rendah dibandingkan siswa yang tidak memahami, menebak-nebak, dan mengalami miskonsepsi sehingga guru harus menangani kelas XII secara maksimal, misalnya dengan merencanakan model dan media pembelajaran terbaik untuk mengatasi rendahnya pemahaman konsep genetik siswa di sekolah.  Kata kunci: certainty of response index (CRI), materi genetika, konsep awal, pemahaman siswaDOI: http://dx.doi.org/10.23960/jpmipa/v24i3.pp627-639